Dinoflagelados del Eoceno Medio a Superior de las cuencas Punta del Este y Colorado, latitudes medias del Atlántico Sudoccidental - Daners, Gloria (2016)
The analysis of middle Eocene dinoflagellate cyst assemblages from sites at Punta del Este (~36°S, Uruguay) and Colorado (~38°S, Argentina) basins allows to interpret ocean circulation patterns on the South American Shelf prior to the opening of the Drake Passage. The assemblages contain endemic-Antarctic taxa such as Enneadocysta, Deflandrea, Vozzhennikovia and Spinidinium, which are also dominant in several circum-Antarctic sites, located southern 45°S. Enneadocysta dictyostila is the most abundant species recorded from the studied sites and the unique member of the endemic assemblage apparently tolerant to warm surface waters. The presence of endemic taxa at mid latitudes has been related to a strong clockwise subpolar gyre favoured by the partial continental blockage of the Tasmanian Gateways and the Drake Passage. The distribution of the dinoflagellate cyst assemblages along the South Atlantic Ocean Shelf can be explained by a similar dynamical mechanism induced by a cyclonic subpolar gyre on the South Atlantic Ocean. The western boundary current of this gyre, starting on the west Antarctic continental slope, would follow a similar path to the present Malvinas Current on the Patagonian slope, which introduce cold oceanic waters to the shelf and intensifies the northward shelf transport. In the same way, during the middle Eocene the western boundary current of a proto-Weddell Gyre transported the circum-Antarctic waters and the endemic taxa northward along the Southwestern Atlantic Shelf. The opening and deepening of the Tasmanian Gateway and Drake Passage and the development of an incipient Antarctic Circumpolar Current during the latest Eocene-Oligocene disrupted the subpolar gyres and promoted the extinction of the endemic species.